Characterizing mineral wettabilities on a microscale by colloidal probe atomic force microscopy. (1st June 2018) - Babel, Bent; Rudolph, Martin
Graphical abstract: Highlights: In-situ characterization of mineral wettabilities on an ore cross section. Microscale characterization of mineral surface wettabilities. Adhesion/hydrophobic imaging was used to visualize varying degrees of hydrophobicity. Limitations are given by probe degradation and topographic inhomogeneities. Abstract: For finely intergrown ores the characterization of reagent-mineral interactions in flotation systems holds difficult challenges for the applicability of standard techniques like Hallimond tube tests or contact angle experiments or renders them impossible, while other techniques might not work in an aqueous environment. We present the utilization of an atomic force microscope with a hydrophobic colloidal probe to characterize the wettabilities of individual mineral grains on a microscale. A sulfidic ore sample containing chalcopyrite, pyrite and quartz is investigated in an aqueous environment. The mineralogy of the sample is characterized by SEM + EDX and its wettability by contact angle measurements. Force mappings on the respective minerals are performed and allow for a distinction between quartz, chalcopyrite and pyrite with the resulting force distributions. An additional focus of this paper lies on the heterogeneities within one mineral surface domain and the applicability for grain mappings.